Increasing age in men is negatively associated with sperm quality and DNA integrity but not pregnancy outcomes in assisted reproductive technology - Xie, Huiyi; Chen, Yikai; Xu, Shangcheng; Miao, Nan; Zheng, Wenwei; Jiang, Chengji; Sun, Tao (Frontiers in Aging, 2025)
As the fertility risks for older males such as infertility and reduced success rates are on the rise, an increasing number of individuals are turning to Assisted Reproductive Technology (ART) to have offspring. However, the influence of paternal age on fertility and pregnancy outcomes in ART cycles remains ambiguous. Here, we analyzed the sperm quality of 6,805 samples and DNA fragmentation index (DFI) of 1,253 samples from Chinese males aged 20–63 years old. Our findings demonstrated that sperm volume, progressive motility, and total motility significantly decline, while sperm DFI increases as paternal age advances. Additionally, by studying 1,205 cases undergoing ART treatment, we discovered that male age and sperm quality do not exhibit a pronounced impact on ART outcomes. Our study has disclosed that sperm quality and DFI are inversely correlated with increasing male age. Our data further suggest that male ages do not significantly affect ART outcomes, which should offer instructive references for ART practice involving older males.